Pembentukan karakter anak usia sekolah melalui surau - Remiswal, Remiswal; Basit, Abdul; Azmi, Fauzan (Ta'dibuna: Jurnal Pendidikan Islam, 2021)
This study aims to get an overview of the role of Surau in the formation of children's character and the forms of internal activities carried out in developing the character formation of school-age children. This study uses a qualitative descriptive approach by revealing all phenomena and meanings naturally. This research successfully explored 1) Surau in the formation of character education for school-age children by carrying out a routine program in the form of discussing the book of the Malay Parukunan in which contains discussion of creeds, morals, and worship as well as reading the Qur'an and following wirid. 2) Form of development of character building for school-age children through surau with the activities of school-age children who are carried out every month has been carried out, besides that the implementation of PHBI activities has been carried out following the schedule listed in the calendar. 3) Supporting factors for the formation of school-age children through surau are: the participation and active role of the community, supporting facilities and infrastructures in every activity carried out by school-age children, such as the presence of chalkboard, microphones, platform, and the room of the mosque big enough to accommodate those present. the attention of the management of the mosque to the activities of school-age children is also one of the factors of the success of the activities carried out. Abstrak Penelitian ini bertujuan mendapatkan gambaran tentang peran Surau dalam pembentukan karakter anak dan bentuk-bentuk kegiatan dalam yang dilaksanakan dalam pengembangan pembentukan karakter anak usia sekolah. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan mengungkap semua fenomena dan makna secara alamiah. Penelitian ini berhasil mengeksplorasikan pertama, surau dalam pembentukan pendidikan karakter anak usia sekolah melaksanakan program rutin berupa membahas kitab Parukunan Malayu. Kedua, bentuk pengembangan pembentukan karakter anak usia sekolah melalui surau dengan adanya kegiatan wirid anak usia sekolah yang dilakukan setiap bulan telah dilaksanakan, di samping itu pelaksanaan kegiatan PHBI telah dilakukan sesuai dengan jadwal yang tertera di kalender. Ketiga, faktor pendukung pembentukan karakter anak usia sekolah melalui surau adalah: adanya partisipasi dan peran aktif dari masyarakat, sarana dan prasarana yang mendukung dalam setiap kegiatan yang dilakukan oleh anak usia sekolah itu, seperti adanya, papan tulis, mikrofon, mimbar dan ruangan surau yang cukup besar untuk menampung para yang hadir. perhatian dari pada pengurus surau terhadap kegiatan anak usia sekolah itu juga merupakan salah satu faktor dari keberhasilan kegiatan yang dilakukan.